Assessment of the prescriptions written in different provinces of Turkey in Terms of drug Utilization Principles [Türkiye'nin farklı illerinde yazılan reçetelerin ilaç kullanımı I.;lkeleri açısından I.;ncelenmesi] - (:unkn) unknown (Marmara University, 2011)
Objective: To learn how physicians' prescribing habits contribute to the rational use of medicine (RUM). We investigated the content of prescriptions written out in different provinces. Material and Method: A total of 3201 prescriptions written in Bartin, Bayburt, Cankiri, Denizli, Eskisehir, Gumushane, Karabuk, Kirsehir, Nevsehir and Nigde were collected from pharmacies. Prescriptions were analyzed using some indicators such as average number of medicines per-prescription (NMPP), average cost per-prescription (CPP) etc. Prescriptions indicating anxiety, hypertension, osteoarthritis, acute (A) otitis media, A.sinusitis, A.tonsillopharyngitis, A.cystitis, diabetes mellitus, dyspepsia and A.diarrhea were evaluated by provinces. Results: Except in three provinces, respiratory drugs were the most commonly written agents. NMPP was highest in Denizli (3.21±0.95), lowest in Cankiri (2.65±1.09). CPP was highest in Denizli (133.35±650.92TRL), lowest in Bartin (42.54±49.91TRL). As for gold standard-compatibility, the prescribed medicines in 4/10 indications seemed better in Cankiri and Gumushane. Injections, antibiotics, analgesics and gastroprotectives were most commonly prescribed in Denizli (14.1%), Kirsehir (43.3%), Gumushane (48.1%) and Bayburt (19.8%) respectively. Conclusion: In the provinces, there were substantial differences in the content of prescriptions. Generally, rational drug prescribing performance was found quite low. These findings should be considered in the activities to the extension of RUM. © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Medicine; Physician; Prescription